Dinámica de elementos en epífitos de un bosque altoandino de la cordillera oriental de colombia (1997)
The reserves and transfer of bioelements were studied during two years in the epiphytic bryophytes and the bromeliad Tillandsia compacta in a high Andean forest in Guisquiza, La Calera, Cundinamarca in the Eastern Andes of Colombia. Epiphyte biomass in this forest is 3766 kg/ha, ofwhich bryophytes contribute 55% and T.compacta, 9.3%. In relation to their biomass, these epihyttes store high quantities of water and nutrients and intercept materials washed from foliage, making them important to consider in watershed management. There are no significant differences in epiphyte element composition between soll and trees, or between size categories of T. compacta. Trapping of heavy elements in particular may mitigate contamination problems in diverse components of the ecosystem. T.compacta appears especially important as a regulator of potassium transfer, and therefore of cation exchange capacity of the system. These properties permit the epiphytes to be dampers of high acidity and of excess concentrations of Al, Fe and Mn common in montant ecosystems, which can be observed in the dynamic model presented.